Pengaruh Penerapan Gaya Mengajar Komando terhadap Peningkatan Kemampuan Passing Menggunakan Kaki Bagian Dalam pada Sepak Bola Siswa di SMP Negeri 6 Tondano - Hermawan Pratama Sakka; JJ Mangindaan; Jan Lengkong (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
This study aims to examine the effect of applying the command teaching style on the ability to kick the ball in soccer among students at SMP Negeri 6 Tondano. The research question is whether the command teaching style can enhance the ability to kick the ball. This experimental study uses a "Randomized Control Group Pre-Test and Post-Test Design." The sample consists of 30 students, divided into an experimental group (15 students) receiving the command teaching style, and a control group (15 students). The study was conducted over one month with sessions held three times a week. The instrument used is the "wall pass test," and the tools include a wall, soccer ball, stopwatch, whistle, and writing materials. Data collection involved pre- and post-tests of the ability to kick the ball, with results recorded and analyzed. Statistical analysis using t-test shows a t-value of 9.98, compared to a critical t-value of 2.48 with 28 degrees of freedom. Since the t-value is greater than the critical t-value, the null hypothesis is rejected, and the alternative hypothesis is accepted. The conclusion is that the command teaching style significantly improves the ability to kick the ball in soccer.